E-014 Effect of carotid artery stenting on cognitive function in patients with carotid artery stenosis: one year outcomes. (16th November 2010) - Turk, A; Pulfer, K; Turski, P; Niemann, D; Aagaard-Kienitz, B; Rowley, H
Abstract : Background: Carotid artery stenosis may be a cause of reduced cognitive performance. We have previously demonstrated that stent revascularization resulted in short term improvement in cognitive testing. The goal of this study was to demonstrate the long term durability of improved cognitive performance 1 year after carotid stenting. Methods: Patients referred for stenting of a unilateral carotid artery stenosis were enrolled in the study. Neuropsychological testing was performed with a Mini-Mental Status Examination, an extended mental status examination, a subjective cognitive status measure and a psychomotor performance speed test. The severity of stenosis was measured on angiography performed prior to stenting. One year after stenting, CT angiography was performed to ensure no restenosis had occurred and neuropsychological testing was repeated. Differences in neuropsychological test scores pre- and post-stenting were calculated and tested for significance with a Student t test. Result: 13 patients with a single unilateral greater than 50% carotid stenosis completed the study. The stenosis of the carotid artery averaged 84% prior to treatment and 9% after treatment. Post-stenting, the extended mental status examination was significantly improved. There was also significant improvement in delayed memory at 1 year that was not present at the 3 month follow-up. The subjective cognitive status measure also improved. No significant change was noted in the Mini-Mental Status Examination or in the speed of psychomotor performance. Conclusion: Carotid artery stenting in patients with a unilateral carotid artery stenosis resulted in significant long term improvements in cognitive test scores, most notably delayed memory.